2021
DOI: 10.1111/ppa.13338
|View full text |Cite
|
Sign up to set email alerts
|

Combined and single effects of elevated CO2 and temperatures on rice bakanae disease under controlled conditions in phytotrons

Abstract: Bakanae disease, caused by Fusarium fujikuroi, was investigated under different CO2 and temperature environments in order to simulate climate changes in the F. fujikuroi–rice pathosystem. F. fujikuroi‐infected plants were grown under six phytotron conditions: low (18/22 °C night/day), medium (22/26 °C), and high (26/30 °C) temperature, at either ambient (450 ppm) or elevated (850 ppm) CO2 concentrations. Bakanae disease index (DI), seedling death incidence, fungal DNA quantity, and chlorophyll and carbohydrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Recent reports have shown increasing disease severity associated with climate change for necrotrophic plant pathogens, such as A. alternata, Cercospora sp., Colletotrichum gloeosporioides, F. equiseti, F. fujikuroi, and F. oxysporum f. sp. conglutinans [334][335][336]. Regarding this review, seven of the tomato plant necrogenic pathogens described, i.e., Bc, Forl, Vd, TSWV, ToMV, PepMV, and PSTVd, have been also reported for their increased pathogenicity or enhanced transmission rates, [19,20,61,63] while up to now, no reports are available for ToBRFV and PMoV.…”
Section: Effect Of Climate Change On Tomato Diseasesmentioning
confidence: 99%
“…Recent reports have shown increasing disease severity associated with climate change for necrotrophic plant pathogens, such as A. alternata, Cercospora sp., Colletotrichum gloeosporioides, F. equiseti, F. fujikuroi, and F. oxysporum f. sp. conglutinans [334][335][336]. Regarding this review, seven of the tomato plant necrogenic pathogens described, i.e., Bc, Forl, Vd, TSWV, ToMV, PepMV, and PSTVd, have been also reported for their increased pathogenicity or enhanced transmission rates, [19,20,61,63] while up to now, no reports are available for ToBRFV and PMoV.…”
Section: Effect Of Climate Change On Tomato Diseasesmentioning
confidence: 99%
“…Recently, the combined effect of CO 2 with temperature on the incidence of bakanae was evaluated. Matić et al (2021) reported that the disease index and death incidence of rice inoculated with the pathogen were elevated under high temperature and CO 2 concentration, with solid support from genetic analysis showing the specific conditions favorable for disease progression. In the disease cycle of bakanae ( Fig.…”
Section: Environmentmentioning
confidence: 94%
“…1 ). Given that the causal agent of bakanae, Fusarium fujikuroi , favors warm and humid climates ( Manandhar, 1999 ; Matić et al, 2021 ), the variable incidences since 2012 were likely to be affected by weather variabilities during the cropping seasons. Moreover, from 2022, the Korea Seed & Variety Service distributes only rice seeds that are not disinfected but promotes the hot water immersion method.…”
Section: Bakanae In Koreamentioning
confidence: 99%
See 2 more Smart Citations